Comparative study of helminth parasites in Mastacembelus armatus (Lacepede, 1800) and Macrognathus pancalus (Hamilton, 1822) collected from fish market of Savar, Dhaka (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not availableJahangirnagar University J. Biol. Sci. 7(1): 73-79, 2018 (June)